The Ethics of Presenting Content on Social Media in the Perspective of Hadith Strong Reprimand for Lying: An Overclaim Case Study - Wulandari, Maslaqha Yunika; fathoniz zakka (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
The phenomenon of overclaims in the skincare industry on social media is the focus of this research because it has an impact on consumer trust and the possibility of disinformation. The selection of this topic is based on an increasing number of exaggerated claims that raise concerns about the health of users that are not supported by scientific evidence. The hypothesis is that honesty contained in Islam can be used to overcome the practice of overclaiming. This research was conducted qualitatively by conducting interviews with customers and industry players and analyzing the content of various social media posts. A study found that many skincare brands often make excessive promises to attract attention, which ultimately leads to dissatisfied customers and a loss of trust. The study also found that people need to be educated about the importance of accurate and honest information when choosing skincare products. The results show that applying the values of honesty is not only important in da'wah but also in contemporary business practices. Therefore, the findings of this study contribute significantly to the advancement of da'wah communication and ethical practices in the cosmetics industry, as well as encourage industry players to be more responsible in providing information to consumers.